Paediatricians' perspectives in treating lower urinary tract symptoms: a qualitative exploratory needs assessment study - Kathleen M Kan; Aditi Sharma; Cati Brown-Johnson; Kritika Sharma; Stav Spinzi; Gunjan Agrawal; Pranaya Venkatapuram (BMJ Publishing Group, 2024)
Background Paediatric lower urinary tract symptoms (LUTS) are common experiences among school-aged children, with prevalence rates reaching as high as 20%. Paediatricians are often first-line stakeholders in providing treatment for these bothersome symptoms, yet there is no formal resource to support them with the treatment of LUTS. Evaluating paediatricians' experiences is an important step in informing health promotion efforts to improve health outcomes in children. This study aims to explore paediatricians' knowledge, beliefs, practice patterns, and perceived barriers and facilitators in providing LUTS care.Methods In this qualitative study, we conducted semistructured focus groups of paediatricians within California. Focus groups were conducted via Zoom, and participants were enrolled until thematic saturation was reached. Participants were asked about their current practices, knowledge and beliefs, barriers and facilitators to care, training and education, and responsibility for behaviour and action. Thematic analysis was performed using deductive and inductive approaches; themes were mapped through an iterative, team-based process.Results 15 paediatricians, aged 30-69 years, with 13 (86.7%) women, were interviewed. Most (11, 73.3%) practised in general outpatient settings. Interviewed paediatricians recognised paediatric LUTS as a common problem that can significantly impact children's well-being. In practice, paediatricians did not actively screen for LUTS beyond the potty-training milestone due to short visit duration and competing healthcare demands. Lack of guidelines, parental mistrust and inadequate clinical education were barriers identified by paediatricians.Conclusions Paediatricians expressed a willingness to help patients but indicated several limitations to providing adequate LUTS care. Future professional development work can emphasise guideline development, early screening strategies to support timely intervention and better education for clinicians.